How Do Transnational Distance Education Graduate Students Perceive Quality? : A Collaborative Autoethnography - Heiser, Rebecca E.; Lazou, Chrysoula; Mavraki, Anastasia; Psychogiou, Maria; Palalas, Aga; Walsh, Pamela (Journal of International Students, 2024)
Driven by competition amongst higher education institutions, increasing recognition of the benefits of international academic mobility, and the global pandemic, transnational distance education has accelerated in recent years. Despite its many advantages, quality assurance issues can pose significant obstacles to success. Using a collaborative autoethnography approach, this study aimed to conceptualize quality dimensions from the perspectives of three Greek graduate students shaped by their collective experience at an open university in Canada. The findings suggest that quality encompasses accessibility, learner-centred instructional design, social-emotional support, and applying acquired knowledge and skills in local contexts.